Penerapan Water Demand Management di Kelurahan Setiamanah, Kota Cimahi - Sri Maryati; Dian Mangiring Arika (Journal of Regional and City Planning, 2008)
Water Demand Management is an effort emphasizing the use of watersupply instead of developing a new supply. This effort is one solution toovercome water supply problems, such as limitation of water resourceand ï¬nancial. Instrument of water demand management applied inIndonesia in general is progressive tariff policy in several PDAM(Public Water Supply Company), nevertheless not all of communitybecome customers of PDAM. How application of water demandmanagement on customer and non customers of PDAM are thequestions explored in this study. The objective of this study isapplication of water demand management by customer and non-customer of PDAM. The study using 114 household consist ofcustomer and non-customer PDAM in Kelurahan Setiamanah, Cimahi.The respondents are, asked about water consumption, willingness toapplying water management instrument, and form of watermanagement instrument already applied. The results of analysis showthat 1) there is no diï¬erence between cunsomer and non cunsomer ofPDAM in water consumption, 2) most of respondents willing to applywater demand management, 3 )respondents who already applied waterdemand management instrument is very limited It can be concludedthat the tarif system in PDAM Kabupaten Bandung have not becomean effective instrument for water demand management. Mostrespondents are generally willing to take steps to conserve water, ifaccess to water resources is very limited.